Vegetative Propagation of PeatT Forest Tree Combretocarpus rotundatus (TUMIH (.Miq) Dancer) with Apical Cutting Methods - Istomo Istomo; Rhomi Ardiansyah; Atok Subiakto (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Cutting is plant propagation system which relatively easy and produces seeds with good quality with the similar characteristics as its parent and takes less time. Until now, the success rooted cuttings of tumih still not known certainly. The research aim is determine the effect of giving the hormone IBA 100 ppm, NAA 100 ppm and combination of IBA 50 ppm and NAA 50 ppm on the growth of Tumih shoots cuttings (Combretocarpus rotundatus (.Miq) Danser). The conclusion that can be taken on the basis of this research was the addition of plant growth regulators (IBA, NAA, and IBA + NAA) has no significant effect on the growth of shoots cuttings Tumih (Combretocarpus rotundatus (.Miq) Danser) so that the use of growth regulators is not needed in breeding of Tumih shoots cuttings (Combretocarpus rotundatus (. Miq) Danser).